Technology Entrepreneurship Insights in New Technology-Based Firms, Research Spin-Offs and Corporate Environments (FGF Studies in Small Business and Entrepreneurship,, 2018)
This collection of expert articles explores the development drivers of new technology-based firms and projects. It provides perspectives for an in-depth understanding of how technological inventions lead to the creation of new and sustainable companies or business units. The authors address methods and concepts that help technology-based start-ups and entrepreneurial projects successfully develop innovative products and services. .